Evaluating and Comparing the Educational, Mystical, Epic Tales using Narrative Therapy - Moridi, Behzad; Rezaee, Somayeh (Journal of History Culture and Art Research, 2017)
Since humankind step into the arena of existence, form of stories, to attract audience and greater impact on them has used. Reader or Hearer of the story, to identify with the hero, the gains experience unquestionably in his attitude to the world and will affect; as far as treatment method called narrative therapy. Stories of classical Persian literature today have the ability to rewrite many simple languages. The stories that exist in different genres can for ethical treatment of disorders, especially in children to be very useful. In this study, Kalīla wa Dimna, Marzubannama and Sindbad-Nameh, educational genres groups, Masnavi and Shaikh Attar’s stories that are a subset of lyrical genre, and the stories of Shahnameh, an epic type were chosen. The reason that these texts, unique examples of the types are mentioned. Then a comparison was made between them in terms of the variety of components and their type finally, it was concluded that messages of any genre compared to other genres, their similarities and differences; but the character is in a dominant genre in the first place is important, in other genres, it is not. Education is a significant component in the "decision-making based on reason and logic" in a kind of mystical, "Punishment of action and see the sins" and the epic genre "pattern of providing confidence and courage".